Empowering Rural Sustainability: Advancing Household-Scale Biogas Reactor Technology with Fiber Reinforced Plastic (FRP) in Suntenjaya Village, Lembang - Parapat, Riny Yolandha; Sudaryanto, Bima Aji; Firdaus, Muhammad Zaki; Hidayat, Windy Nur Ramadhani Putri; Kurniawan, Ronny; Yuono, Yuono; Harjaya, Immanuel Teja (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Rural communities require appropriate technology to process livestock waste that has been polluting the environment, particularly water bodies such as rivers. Biogas technology offers a solution by converting waste into renewable energy, namely biogas, which can be utilized for daily needs and high-quality organic fertilizer production. Unfortunately, the biogas reactors currently in use were developed over 50 years ago without significant innovations. Hence, there is a pressing need for a more efficient (affordable and user-friendly) and effective (in terms of performance) biogas reactor technology suitable for rural communities—specifically, the Fiber Reinforced Plastic (FRP) biogas reactor technology. The objective of this endeavor is to create a household-scale prototype FRP biogas reactor, designed according to specific requirements and standardized for widespread use. This prototype will be implemented and tested in the field, allowing for dissemination to a broader audience. For modeling purposes, the FRP reactor design will be applied in a demonstration plot in Sunten Jaya Village, Lembang Subdistrict, West Bandung Regency. The results from the demonstration plot reveal that the produced biogas amounts to 40 L/kg of cow dung.